2016
DOI: 10.3390/molecules21040495
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Antagonists Used for Determining the Mechanisms of Action Employed by Potential Vasodilators with Their Suggested Signaling Pathways

Abstract: This paper is a review on the types of antagonists and the signaling mechanism pathways that have been used to determine the mechanisms of action employed for vasodilation by test compounds. Thus, we exhaustively reviewed and analyzed reports related to this topic published in PubMed between the years of 2010 till 2015. The aim of this paperis to suggest the most appropriate type of antagonists that correspond to receptors that would be involved during the mechanistic studies, as well as the latest signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 332 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Endothelium-derived relaxing factors (EDRFs) as well as endothelium-derived contracting factors (EDCFs) elicit their vascular actions through interaction between the endothelium and vascular smooth muscle cells. 8 Responses elicited by endothelium-derived relaxing factors are usually studied, in vitro, in arterial rings precontracted with phenylephrine or noradrenaline. In endothelium-denuded rings, endothelium-dependent relaxation response to acetylcholine (Ach) is impaired.…”
Section: Vascular Endotheliummentioning
confidence: 99%
See 3 more Smart Citations
“…Endothelium-derived relaxing factors (EDRFs) as well as endothelium-derived contracting factors (EDCFs) elicit their vascular actions through interaction between the endothelium and vascular smooth muscle cells. 8 Responses elicited by endothelium-derived relaxing factors are usually studied, in vitro, in arterial rings precontracted with phenylephrine or noradrenaline. In endothelium-denuded rings, endothelium-dependent relaxation response to acetylcholine (Ach) is impaired.…”
Section: Vascular Endotheliummentioning
confidence: 99%
“…In endothelium-denuded rings, endothelium-dependent relaxation response to acetylcholine (Ach) is impaired. 8,9 It has been extensively reported that in endothelium-intact rings, Ach-induced relaxation is completely reversed by NG-nitro-Larginine-methylester (L-NAME); a selective inhibitor of nitric oxide synthase. 1 In vascular tone regulation, both endothelium-derived relaxing factors (EDRFs) and endothelium-derived contracting factors (EDCFs) produce their effect via interaction between the endothelium and vascular smooth muscle cells.…”
Section: Vascular Endotheliummentioning
confidence: 99%
See 2 more Smart Citations
“…However, before the vasculature-related research is carried out, the signaling mechanism pathways happening in the vasculature should be clearly understood. Previous reviews have shown that aortic ring assay is recommended as the “golden tool” in most of the in vitro pharmacological research, especially those related to vasculature, along with the protocols and suggested antagonists that are to be used for different mechanism studies [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%